2007
DOI: 10.1371/journal.pbio.0050218
|View full text |Cite
|
Sign up to set email alerts
|

Tetrameric Structure of Centromeric Nucleosomes in Interphase Drosophila Cells

Abstract: Centromeres, the specialized chromatin structures that are responsible for equal segregation of chromosomes at mitosis, are epigenetically maintained by a centromere-specific histone H3 variant (CenH3). However, the mechanistic basis for centromere maintenance is unknown. We investigated biochemical properties of CenH3 nucleosomes from Drosophila melanogaster cells. Cross-linking of CenH3 nucleosomes identifies heterotypic tetramers containing one copy of CenH3, H2A, H2B, and H4 each. Interphase CenH3 particle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

18
244
3

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 218 publications
(265 citation statements)
references
References 53 publications
18
244
3
Order By: Relevance
“…This finding confirms that DNA wraps only once around a Cse4-containing core (33), as implied by our previous study showing that Cse4 nucleosomes induce positive supercoiling at functional centromeres in vivo (6). Our findings are consistent with the observation that singly wrapped CenH3 particles also occupy Drosophila and human centromeres (8,9), suggesting that this organization is a universal feature of centromeric nucleosomes. Singly wrapped tetrameric nucleosomes are universal for archaea (34), as if centromeres have retained the ancestral nucleosomal organization.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This finding confirms that DNA wraps only once around a Cse4-containing core (33), as implied by our previous study showing that Cse4 nucleosomes induce positive supercoiling at functional centromeres in vivo (6). Our findings are consistent with the observation that singly wrapped CenH3 particles also occupy Drosophila and human centromeres (8,9), suggesting that this organization is a universal feature of centromeric nucleosomes. Singly wrapped tetrameric nucleosomes are universal for archaea (34), as if centromeres have retained the ancestral nucleosomal organization.…”
Section: Discussionsupporting
confidence: 92%
“…Most important is the histone variant, CenH3 (CENP-A in mammals and Cse4 in yeast), which replaces histone H3 in centromeric nucleosomes and is essential for recruitment of the other structural components of the kinetochore (5). It has been previously shown that the Cse4 nucleosome wraps DNA in a right-handed orientation (6,7), consistent with in vivo observations of heterotypic tetrameric nucleosomes in Drosophila (8) and humans (9). However, several studies have shown that CenH3 nucleosomes are left-handed octamers in vitro (10)(11)(12)(13)(14).…”
supporting
confidence: 77%
“…Experimental evidence in favor of a histone tetramer [hemisome; H2A/H2B/H4/(CenH3 = Cse4)] or a histone octamer (H2A/H2B/H4/CenH3/CenH3/H4/H2B/ H2A) has been reported (22,25,(28)(29)(30). The specter of an unusual hexameric nucleosome core, bereft of H2A and H2B, but including the Cse4-associated nonhistone protein Scm3 [H4/ Cse4/Cse4/H4-(Scm3)2], has also been raised (31).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, histones H3 and H4 were found as dimers together with histone chaperones within predeposition complexes in human cells . Moreover, the investigation of CenH3 (centromeric-specific H3) nucleosomes identified hemisomes containing one copy each of CenH3, H2A, H2B, and H4 (Dalal et al 2007). Together these data suggest that histones H3 -H4 or CenH3 -H4 can be first provided as dimers.…”
Section: Stoichiometry Of Histone Depositionmentioning
confidence: 99%